Non-compaction and dilated cardiomyopathy: genotypic, phenotypic and prognostic differences - T. G. Vaykhanskaya; L. N. Sivitskaya; O. D. Levdansky; T. V. Kurushko; N. G. Danilenko (Российский кардиологический журнал)
Aim. To study and compare genotypic and phenotypic signs in patients with non-compaction cardiomyopathy (NCM) and dilated cardiomyopathy (DCM), to conduct a comparative analysis of clinical outcomes and 5-year cumulative survival of patients with NCM and DCM.Material and methods. The study included 144 unrelated patients with cardiomyopathy: NCM (n=74) and DCM (n=70). Mean age was 39 [30; 49] years (men, 96 (66,7%); left ventricular ejection fraction (LVEF) was 30,5 [24; 46]%. A comprehensive clinical examination included electrocardiography, Holter monitoring, echocardiography, cardiac magnetic resonance imaging, coronary angiography, DNA diagnostics (NGS+Sanger), cascade screening, and cosegregation analysis. To assess clinical outcomes, the NCM group was divided into 2 subtypes according to baseline LV systolic function (NCM/DCM phenotype — 50 individuals with LVEF ≤49%; and isolated NCM — 24 patients with LVEF ≥50%). The following adverse events were assessed as the composite endpoint: cardiovascular death, heart transplantation (HT), sustained ventricular tachycardia, ventricular fibrillation, successful cardiopulmonary resuscitation, cerebral thromboembolism. The follow-up period was 62 months.Results. Among patients with LVEF ≤49% at a 5-year follow-up, 37 (74,0%) of 50 patients with the NCM/DCM phenotype and 41 (58,6%) of 70 patients with DCM achieved composite endpoint. Out of 24 patients with NCM with LVEF ≥50% (median LVEF, 56 [51; 61]%), 2 (8,3%) patients achieved composite endpoint (χ2=28,8; p=0,001). In the NCM/DCM group with LVEF ≤49%, a higher level of pathogenic genetic variants (64% vs 41,4%/DCM vs 29,2%/NCM; χ2=11,4; p=0,003), cerebral thromboembolism (χ2=11,8; p=0,003) and HT (χ2=10,6; p=0,005). The results of the 5-year survival analysis (Kaplan-Meier) showed a worse prognosis for NCM with LVEF ≤49% compared with DCM (log rang: χ2=11,5; p=0,001) and isolated NCM (log rang: χ2=17,02; p=0,0001). In the overall cohort (n=144), gene-positivity was also associated with worse prognosis (log rang: χ2=5,38; p=0,02).Conclusion. In the present study, patients with dilated subtype of NCM showed a worse prognosis compared with DCM and isolated NCM. Heart failure progression and cerebral thromboembolism were the most common complications in patients with NCM/DCM.